EFFECT OF SALINITY ON GROWTH AND BIOPIGMENT COMPOSITION OF DUNALIELLA SALINA ISOLATED FROM SAMBHAR SALT LAKE, RAJASTHAN, (INDIA) - PRIYANKA DHAKA; GAJENDRA PAL SINGH (International Journal of Pharma and Bio Sciences, 2016)
A study was conducted to investigate the impact of salinity (NaCl) on the growth and biopigment of a green alga Dunaliella salina isolates from Sambhar salt lake, Rajasthan (India). In order to determine the impact of NaCl, an algal species D. salina was exposed to different concentrations of NaCl ranging from 1M to 5M along with control (1.5M) over a period of 30 days. It was found that the algal biomass yield was highest at 2M NaCl concentration and then it subsequently decreases with increase in NaCl concentration. Total chlorophyll content of the algal species decreases as the salinity was increased. While total carotenoids content of the algal species increases as the increases salt concentration and it was found that the green alga species changed its appearance from green to deep orange. The results indicated that algal species showed diverse response to salinity stress.